Propuesta gastronómica a través de un recetario para fomentar el consumo del hongo ostra rosado en la población de Ibarra - Cano Vargas, Michael Ismael (2024)
This research focuses on the development of a culinary recipe book to promote the consumption of the pink oyster mushroom (Pleurotus djamor) among the population of Ibarra. The main objective was to create an attractive culinary offering that increases the use of this mushroom, known for its high nutritional value and versatility in cooking. The methodology included a comprehensive review of important aspects of the pink oyster mushroom and its culinary applications, followed by experimentation with various recipes. Qualitative and quantitative methods, including surveys and interviews with inhabitants of Ibarra, were employed to assess the knowledge, current consumption, and perception of the pink oyster mushroom. The results revealed that although the majority of respondents are unaware of this mushroom and do not consume it regularly, there is a positive disposition towards incorporating it into their diet through a recipe book. Additionally, barriers such as the lack of knowledge about its preparation and nutritional benefits were identified. In conclusion, this research provided a solid foundation for promoting the pink oyster mushroom as a nutritious and versatile food in the kitchen. Various cooking techniques were documented, notably sautéing, roasting, and baking, among others. The results suggest that including the pink oyster mushroom in the daily diet could have significant health and nutritional benefits for each person who adopts it. Future studies should focus on expanding the sample and evaluating the long-term impact of oyster mushroom consumption on health.